KiKli Fit: Research and Practice in Physical Activity for Acute Pediatric Cancer - Valentin Johannes Benzing (Current Issues in Sport Science)
While survival rates for pediatric cancer have improved significantly, the disease and its treatments often lead to severe side effects and long-term physical and mental health challenges. Evidence suggests that physical activity can positively influence multiple health domains, even during the acute treatment phase. This session will provide research on a) the benefits of physical activity for physical and mental health in children with cancer, b) the practical implementation of the KikliFit project within the acute treatment phase, and c) the accompanying implementation research that evaluates and informs the integration of physical activity into practices.